Low-Carbon Supplier Selection Using Fuzzy AHP and Goal Programming Approach - Feipeng Huang (Discrete Dynamics in Nature and Society)
It has become the leading world trend that all countries join hands to respond to climate change and promote green and low-carbon development. In this background, more and more enterprises seek to control carbon emissions from the source and reduce indirect carbon emissions, consequently paying increased importance to the carbon footprint of their suppliers. Most of the earlier studies concerning supplier selection mainly focus on traditional factors, such as quality, service, and lead time, but minimal importance to the carbon emission of supplies. This study fills this gap by incorporating carbon emission criteria into supplier selection and presenting a method of combining fuzzy analytic hierarchy process (AHP) and fuzzy goal programming (GP) to address the problem of supplier selection and order quota allocation. Firstly, we use fuzzy AHP to evaluate the relevance and importance of supplier selection criteria according to the experts’ opinions. Second, each objective is given weights according to the fuzzy AHP results, and then the fuzzy GP method is used for supplier selection and order quota allocation. Finally, we implement an example study with a data set from a realistic situation, and the results confirm the effectiveness of the proposed method in an uncertain environment.